2016 IEEE 16th International Conference on Environment and Electrical Engineering (EEEIC) 2016
DOI: 10.1109/eeeic.2016.7555474
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative braking in high speed railway applications: Analysis by different simulation tools

Abstract: Abstract-Technical investigations continuously evaluate the possibility to recover significant amount of braking energy. The application normally involve conventional tramways, characterized by several stops in short-range routes. However, this possibility is becoming more and more attractive also when high-speed trains are considered. In fact, braking energy can be recovered during entry in the station, and delivered later to other trains engaged in starting acceleration. In this work, authors propose an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Using for‐loops such as this one, it is easy to create an electric network connecting a generic number of FSSs and trains and even do more complex tasks, for instance, creating two‐way railway networks. This was, for instance, effectively done when performing studies …”
Section: Technical Issues Tackled and Solvedmentioning
confidence: 99%
See 3 more Smart Citations
“…Using for‐loops such as this one, it is easy to create an electric network connecting a generic number of FSSs and trains and even do more complex tasks, for instance, creating two‐way railway networks. This was, for instance, effectively done when performing studies …”
Section: Technical Issues Tackled and Solvedmentioning
confidence: 99%
“…Under this general hypothesis, it was obtained from simulation full energy savings equal to about 797 MWh per year . The quantification of the corresponding money advantage has been calculated by considering the current price of energy in Italy and storage system costs.…”
Section: Summarizing Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation has been performed considering a traction phase of the train in a brief part of the line. Then, the model realised in Modelica language has been validated on the same case study, as shown in [30].…”
Section: Introductionmentioning
confidence: 99%